Analysis of Criminal Action Settlement for Negligence in Traffic that Resulting in the Loss of Other People's Life - Ngatno Ngatno; Siti Ummu Adillah; Widayati Widayati (Universitas Islam Sultan Agung, 2022)
This study aims to find out and analyze the settlement of criminal acts of negligence in traffic which resulted in the loss of other people's lives in case number 24/Pid.Sus/2020/PN Kds and to find out and analyze how the judge's legal considerations in making decisions on negligence offenses traffic that resulted in the loss of other people's lives in case number 24/Pid.Sus/2020/PN Kds. This research is a sociological juridical research by combining legal materials (which are secondary data) with primary data obtained in the field. Based on the research, it is concluded that the analysis of the settlement of criminal acts in traffic that resulted in the loss of other people's lives in Case Number 24/Pid.Sus/2020/PN Kds based on the theory of punishment, there are several processes for handling criminal cases by law enforcement in order to conduct investigations, investigation, arrest, detention, prosecution and imposition of criminal sanctions. The judge's legal considerations in passing a decision on the offense of traffic negligence which resulted in the loss of another person's life in Case Number 24/Pid.Sus/2020/PN the existence of Kds is that the panel of judges saw an element of criminal responsibility in the case of driver negligence that caused a traffic accident as follows: (1) must commit a crime, (2) be able to take responsibility (3) intentionally or negligently (4) there is no excuse for forgiveness. The judge in imposing a prison sentence of 1 year and three months and a fine of IDR 5,000,000 for the actions of the perpetrators according to the researcher is still not optimal.